Sosialisasi Model Lokasi Evakuasi Untuk Mitigasi Gempa Bumi Di Siten, Desa Sumbermulyo, Kapanewon Bambanglipuro, Kabupaten Bantul - Fivry Wellda Maulana; Rakhman, Arie Noor (DHARMA BAKTI, 2022)
Community service activities were carried out in Siten, Sumbermulyo Village, Kapanewon Bambanglipuro, Bantul Regency. The counseling was attended by members of the Family Empowerment and Welfare (PKK) group. Since the 2006 great earthquake, the public has been educated on earthquake response. However, they do not know the relationship between geological features and the value of local wisdom. Earthquakes of small scale and intensity are still being felt. Through service activities, the participants understand the emergency location planning model after the earthquake disaster. The introduction of local wisdom values ​​in the existence of several places becomes a means of educating the existence of geological features in the earthquake disaster area. Some of these places include springs, historical heritage sites, and isolated hill of Gunung Cilik. Based on the optimization of the results of previous research on geological features and Google Earth, an earthquake evacuation location is recommended. Evacuation locations are directed at limestone hills, 1 km to the west from the service location. Google Map can be used by participants to identify the evacuation route. In the discussion, a simulation of the evacuation was proposed to be carried out